1996
DOI: 10.1046/j.1365-2761.1996.d01-96.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rainbow trout, Oncorhynchus mykiss (Walbaum), serum creatine kinase isoenzymes and isoforms by means of electrophoresis and isoelectric focusing

Abstract: Serum samples were obtained from rainbow trout, Oncorhynchus mykiss (Walbaum), from a commercial fish farm. Creatine kinase (CK; EC 2.7.3.2) isoenzymes and sub-bands (isoforms) were studied using agarose gel electrophoresis and polyacrylamide gel isoelectric focusing. Creatine kinase isoenzymes and isoforms (sub-bands) were found to display disparate electrophoretic mobility and isoelectric points, respectively, when compared with CK patterns of human origin. The CK-BB isoenzyme, rarely detected in human serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In fact there is no significant difference between the two, both from a morphological and a commercial point of view. We selected IEF on broad pH (3.5-9.5) polyacrylamide gels, as it is a well-established and widely utilized [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], while relatively simple, [14,19], although recently improved analytical strategies have been developed (for example, using parvalbumins as proteins of choice in fish identification [20]), performing the electrophoretic run with either CleanGels or immobilized pH gradient gels, IPGs [21]. Many less valuable shark species are sold under the generic name "smoothhound", thus committing fraudulent substitution by mislabeling the products.…”
mentioning
confidence: 99%
“…In fact there is no significant difference between the two, both from a morphological and a commercial point of view. We selected IEF on broad pH (3.5-9.5) polyacrylamide gels, as it is a well-established and widely utilized [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], while relatively simple, [14,19], although recently improved analytical strategies have been developed (for example, using parvalbumins as proteins of choice in fish identification [20]), performing the electrophoretic run with either CleanGels or immobilized pH gradient gels, IPGs [21]. Many less valuable shark species are sold under the generic name "smoothhound", thus committing fraudulent substitution by mislabeling the products.…”
mentioning
confidence: 99%
“…Williams et al (1996) reported plasma CK isoenzyme patterns of healthy rainbow trout. It is known that the severe myopathy in "Sudden death syndrome" of Atlantic salmon was accompanied by a significant elevation of CK activity levels (Rodger et al, 1991).…”
mentioning
confidence: 99%